The Impact of Child Victims 'Behavior on Judges' Light Vantages for Persons of Criminal Acts of Ability or Abuse - Betra Sarianti; JT Pareke (Jurnal Penegakan Hukum Indonesia, 2022)
The Child Protection Act has given severe sanctions to perpetrators of sexual intercourse and obscene acts as regulated in Article 81 and Article 82 of the Child Protection Law with a minimum penalty of 5 years and a maximum of 15 years in prison. This study aims to determine whether the behavior of the victim's child is considered by the judge in passing a verdict on the perpetrator of sexual intercourse/obscenity and what is the basis for the judge's authority to decide cases based on the provisions of the law. The method used in this study is a normative legal research method (juridical normative) using a statute approach, a conceptual approach, and a case approach. The results of the study show that the behavior of the victim's child becomes the judge's consideration in deciding on the perpetrator. If the victim can prove that the child knows that intercourse is prohibited, and there is no attempt to refuse and continue to do, even accept something from the perpetrator, the judge will give a lighter sentence to the perpetrator of sexual intercourse/obscenity, not by the provisions of Articles 81 and 82 of Child Protection, which is at least 5 years in prison. The judge's authority to decide cases of criminal acts of sexual intercourse or obscenity based on the provisions of the law is regulated in Article 24 paragraph (1) of the 1945 Constitution in conjunction with Article 1 paragraph (1) of Law Number 48 of 2009 concerning Judicial Power which states that judges have the freedom to implement justice for the sake of law and justice.